Sucrosomial® Iron: A New Generation Iron for Improving Oral Supplementation - Susana Gómez-Ramírez; Elisa Brilli; Germano Tarantino; Manuel Muñoz (MDPI AG, 2018)
Iron deficiency (ID) is usually treated with oral iron salts, but up to 50% of patients complain of gastrointestinal side effects, leading to reduced compliance with treatment. Intravenous (IV) iron formulations are increasingly safe, but there is still a risk of infusion, hypersensitivity reactions and the need for venous access and infusion monitoring. Sucrosomial® Iron (SI) is an innovative oral iron formulation in which ferric pyrophosphate is protected by a phospholipid bilayer plus a sucrester matrix (sucrosome), which is absorbed through para-cellular and trans-cellular routes (M cells). This confers SI’s unique structural, physicochemical and pharmacokinetic characteristics, together with its high iron bioavailability and excellent gastrointestinal tolerance. The analysis of the available evidence supports oral SI iron as a valid option for ID treatment, which is more efficacious and tolerable than oral iron salts. SI has also demonstrated a similar effectiveness, with lower risks, in patients usually receiving IV iron (e.g., chronic kidney disease, cancer, bariatric surgery). Thus, oral SI emerges as a valuable first option for treating ID, especially for subjects with intolerance to iron salts or those for whom iron salts are inefficacious. Moreover, SI should also be considered as an alternative to IV iron for initial and/or maintenance treatment in different patient populations.